2014
DOI: 10.3852/13-226
|View full text |Cite
|
Sign up to set email alerts
|

Peltaster cerophilus is a new species of the apple sooty blotch complex from Europe

Abstract: Adopting the currently used concept for the genus Peltaster, the sooty blotch fungus Peltaster cerophilus is newly described from the cuticle of ripening or ripe apples. It forms a punctate phenotype consisting of superficially formed pycnothyria and a superficial mycelial mat consisting of a net of brown or brownish black hyphae. The pycnothyria are olivaceous brown to brown but have a spot in the center that is less strongly pigmented. Pycnothyria on the holotype of P. fructicola are homogeneously pigmented.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…It also causes SBFS signs on fruit of pawpaw ( Asimina triloba ) in Iowa, USA 6 and crabapple ( Malus × micromalus ) and hawthorn ( Crataegus pinnatifida ) in China 7 . Although P. fructicola was classified within the Capnodiales along with most other SBFS species, the genus Peltaster , including another recently established species P. cerophilus , seems to be an isolated lineage 2 8 9 . Research on P. fructicola has focused mainly on its taxonomy, biogeography, pathogenicity, control by fungicides, and responses to temperature, humidity, and nutrients 10 11 12 13 14 15 .…”
mentioning
confidence: 99%
“…It also causes SBFS signs on fruit of pawpaw ( Asimina triloba ) in Iowa, USA 6 and crabapple ( Malus × micromalus ) and hawthorn ( Crataegus pinnatifida ) in China 7 . Although P. fructicola was classified within the Capnodiales along with most other SBFS species, the genus Peltaster , including another recently established species P. cerophilus , seems to be an isolated lineage 2 8 9 . Research on P. fructicola has focused mainly on its taxonomy, biogeography, pathogenicity, control by fungicides, and responses to temperature, humidity, and nutrients 10 11 12 13 14 15 .…”
mentioning
confidence: 99%
“…The recently described species Peltaster cerophilus (Medjedović et al 2014) has been demonstrated to be the most important sooty-blotch fungus affecting organic orchards within the two largest German production areas of the Lower Elbe region in the north and the Lake Constance area in the south (R.W.S. Weber, unpublished).…”
Section: Discussionmentioning
confidence: 99%